Sistema informático basado en internet de las cosas para el monitoreo de variables físicas y químicas en el río Amazonas en Loreto-Perú - Mozombite Panduro, Jennifer Yordanka (2024)
This research exposes the results of the design, construction and validation of an IoT-based device, which aims to support the process of monitoring physical and chemical variables in bodies of water such as the Amazon River, through a web platform that allows the real-time visualization of these variables. A Report has been implemented that visualizes an IoT device located at monitoring points in the Amazon River. Observation Sheets have been used to evaluate the system indicators. This research is of Applied type, experimental design. The results obtained have indicated optimal functioning of the IoT device connected to the information system at the monitoring points at the defined hours. In conclusion, the implementation of low-cost IoT devices are support tools that at a lower cost can resolve the limitations of monitoring and the lack of alternatives to support these processes, serving institutions and specialists who need to study the variables. physical-chemical characteristics of water.